Contemporary Paintings from Yugoslavia. (Seoul : National Museum of Contemporary Art, 1990)
Spanzel, Rudi ; Jordan, Vasilije ; Stanic, Vojo ; Ivancic, Ljubo ; Vrkljan, Zlatan ; Protic, Miodrag B. ; Knifer, Julije ; Salamun, Andraz ; Ivackovic, Dorde ; Jeraj, Zmago ; Seder, Duro ; Keser, Zlatko ; etc.
Contemporary Paintings from Yugoslavia, The National Museum of Contemporary Art, Seoul, 19.04. - 02.06.1990
boek
Keywords: Joegoslavië